Association Between Dioxin and Metabolic Syndrome by Age and Sex in an Endemic Area of Exposure in Taiwan. (October 2017) - Huang, Chien-Yuan; Lee, Ching-Chang; Chang, Jung-Wei; Cheng, Ya-Yun; Kuo, Yau-Chang; Guo, How-Ran; Wu, Chen-Long
Abstract : Background: Some of the effects of dioxins seem to be different between men and women, and exposures starting at an early age seem to have more prominent effects. Therefore, we conducted a study in Taiwan to evaluate the associations between exposure to polychlorinated dibenzo- p -dioxins and dibenzofurans (PCDD/Fs) and metabolic syndrome (MetS) starting at different ages in both sexes. Methods: We recruited participants from an area where residents were exposed to PCDD/Fs released from a factory and defined serum PCDD/Fs levels ≥20 pg WHO98 -TEQDF /g lipid as high dioxin levels. MetS was defined as meeting three of the following criteria: fasting glucose ≥100 mg/dl or under treatment for diabetes, waist circumference ≥90 cm in men or ≥80 cm in women, triglycerides ≥150 mg/dl or under treatment for elevated triglycerides, high-density lipoprotein <40 mg/dl in men or <50 mg/dl in women, and blood pressures ≥130/85 mmHg or under treatment for hypertension. Results: Of the 2758 participants, 785 patients with MetS were identified, and we observed positive associations between a high dioxin level and MetS. After adjusting for sex, age, and age at starting exposure, we found that a high dioxin level was an independent predictor for MetS (adjusted odds ratio =1.38; 95% confidence interval = 1.11, 1.72). When we stratified the participants by gender, we found that a high dioxin level remained an independent predictor of MetS in men, but not in women, regardless of the age at starting exposure. Conclusions: Exposure to PCDD/Fs was associated with MetS in men, independent of age and age at starting exposure.